(934) theories of social change and edited selection from the writing of current authors نظريات التغيير الاجتماعي ومختارات محررة من كتابات مؤلفين معاصرين - Abd El Aziz M, Salem; W.A. Hassona (INP, 2024)
The concept of change has captivated philosophers and theologians throughout history, shaping entire metaphysical systems. Thinkers like Al-Ghazali influenced the scholasticism of Thomas Aquinas, while Parmenides and Augustine of Hippo viewed change as a process. Some have regarded change as a natural phenomenon governed by universal laws, while others see it as a force for social progress, provided it maintains reverence for life. Today, the topic of change continues to engage modern minds with the same intensity as Aristotle’s distinctions between substantial and accidental change once did.